2023
DOI: 10.1038/s41598-023-33822-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of vB_AbaM_PhT2 phage hydrophobic amino acid fusion endolysin, combined with colistin against Acinetobacter baumannii

Abstract: Phage lytic enzymes are promising antimicrobial agents. In this study, an endolysin derived from vB_AbaM_PhT2 (vPhT2), was identified. This endolysin represented the conserved lysozyme domain. Recombinant endolysin (lysAB- vT2) and hydrophobic fusion endolysin (lysAB-vT2-fusion) were expressed and purified. Both endolysins showed lytic activity against bacterial crude cell wall of Gram-negative bacteria. The MIC of lysAB-vT2-fusion was 2 mg/ml corresponding to 100 µM, while the MIC of lysAB-vT2 was more than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…Notably, polymyxins primarily target bacterial membranes, disrupting their integrity and inducing cell death, rendering them as last-resort antibiotics for Gram-negative bacteria ( Briers et al, 2014 ). This finding aligns with the study by Sitthisak et al (2023) , which reported a synergistic interaction between an engineered endolysin from phage vB_AbaM_PhT2 and colistin against A. baumannii , with a FICI of 0.25. Similarly, the engineered EC340, derived from phage PBEC131 infecting Escherichia coli , demonstrated a synergistic effect exclusively with colistin and an additive effect with meropenem, tigecycline, chloramphenicol, azithromycin, and ciprofloxacin ( Hong et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Notably, polymyxins primarily target bacterial membranes, disrupting their integrity and inducing cell death, rendering them as last-resort antibiotics for Gram-negative bacteria ( Briers et al, 2014 ). This finding aligns with the study by Sitthisak et al (2023) , which reported a synergistic interaction between an engineered endolysin from phage vB_AbaM_PhT2 and colistin against A. baumannii , with a FICI of 0.25. Similarly, the engineered EC340, derived from phage PBEC131 infecting Escherichia coli , demonstrated a synergistic effect exclusively with colistin and an additive effect with meropenem, tigecycline, chloramphenicol, azithromycin, and ciprofloxacin ( Hong et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…And to slow the spread of antibiotic resistance by using fewer antibiotic treatments of low dosages ( Lai et al, 2020a ). Combined use of endolysin LysAB-vT2-fusion with colistin, polymyxin B, or copper showed synergistic against A. baumannii , which may be used for the control of A. baumannii infection ( Sitthisak et al, 2023b ).…”
Section: Antimicrobial Resistancementioning
confidence: 99%